Sustainability Status Of Squid Fishery Business Using Boat Lift Nets Based On Bioeconomics In Ekor Village, East Halmahera Regency - Karman, Amirul; Surahman, Surahman; Abd. Mutalib, Nurhasna; Kaidati, Bahar; Hi. Iksan, Kusdi; Subur, Riyadi (Agrikan Jurnal Agribisnis Perikanan, 2023)
Squid fishing business is an activity to exploit squid resources with the aim of obtaining a continuous profit. The aim of the research was to analyze the biological aspects which include the structure of the length of the mantle and the size suitable for catching as well as the percentage of the size of the squid that is suitable for catching; analyze economic aspects; and analyze the status of a sustainable squid fishery business. The research was conducted in Ekor Village, South Wasile District, East Halmahera Regency for 7 days, from 7 to 13 December 2022. The research method used was a survey method. The structure of the length of the mantle of the squid caught in the boat net was dominated by the size suitable for catching, namely 57.17% and the size not suitable for catching, by 42.83%. Financially and investment, the squid fishing business with a boat chart is feasible to be cultivated throughout the year, with a profit value of IDR. 53,303,000.00, B/C ratio 1.12, IRR 33%, BEP IDR. 152,576,999, and PP 3.78 years. The squid fishing business with a boat chart based on biological and economic aspects (financial and investment criteria) in Ekor Village, South Wasile District, East Halmahera Regency has high sustainability.